Perkembangan Industri Batik Cigeureung Kota Tasikmalaya Tahun 2000–2015: Tinjauan Historis dan Ekonomi Kreatif - Wulan Sondarika; Dewi Ratih; Egi Nurholis; Hana Haniyyah; Hilman Januar; Cecep Husnan Abdul; Iis Aisah; Galurawati Candra (Universitas Galuh, 2023)
This study examines the historical development and creative economy dynamics of the Cigeureung batik industry in Tasikmalaya City, addressing a critical gap between economic history and local creative industry studies. Existing batik research predominantly focuses on major production centers in Java, while historically grounded analyses of peripheral batik industries remain limited. Employing a historical method with a qualitative approach encompassing heuristics, source criticism, interpretation, and historiography this study reveals that the Cigeureung batik industry has transformed from a traditional household-based activity into an adaptive creative industry integrating design innovation, production strategies, and digital marketing. Despite this progress, sustainability is constrained by structural challenges, including competition from mass-produced textiles and weak artisan regeneration. This study contributes to advancing economic history perspectives within the discourse of culture-based creative industries.